A Bifacial Point of Extraordinary Dimensions Found in Paraná State, Southern Brazil. (2nd January 2021) - Parellada, Claudia; Parenti, Fabio; Okumura, Mercedes
ABSTRACT: We present in this article the description of a bifacial point found in the municipality of Boa Ventura de São Roque, in the state of Paraná, southern Brazil. Given that it is a piece of exceptional size, made with a complex manufacturing technique, we made a metric description and analysis of the knapping technique of this artifact, in order to compare it with other similar artifacts found in Brazil.